2012
DOI: 10.1210/jc.2011-1999
|View full text |Cite
|
Sign up to set email alerts
|

Normalizing Eating Behavior Reduces Body Weight and Improves Gastrointestinal Hormonal Secretion in Obese Adolescents

Abstract: Retraining obese adolescents to eat more slowly has a significant impact on the gastrointestinal hormone response to a carbohydrate load, suggesting that externally modifiable eating behaviors actually regulate the hormonal response to food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 31 publications
2
59
2
2
Order By: Relevance
“…The Use of the Mandometer Bergh, Södersten and colleagues have developed a device which they call the Mandometer that provides patients with feedback on their rate of eating [48][49][50][51][52] . In several publications these investigators have reported that providing patients with such feedback can either accelerate or decelerate the rate of eating behavior, increasing the rate in those who eat too slowly, while decelerating it in those who eat too quickly.…”
Section: Other Biological Therapiesmentioning
confidence: 99%
“…The Use of the Mandometer Bergh, Södersten and colleagues have developed a device which they call the Mandometer that provides patients with feedback on their rate of eating [48][49][50][51][52] . In several publications these investigators have reported that providing patients with such feedback can either accelerate or decelerate the rate of eating behavior, increasing the rate in those who eat too slowly, while decelerating it in those who eat too quickly.…”
Section: Other Biological Therapiesmentioning
confidence: 99%
“…Manipulation of bite size may be achieved through changing the shape of foods [57], using utensils that support smaller bites [51] and by changing the textures of foods to reduce eating rate and energy intake [11,58,59]. Changes to eating rate can be produced by prompting the eater via external monitors of eating rate; this has been shown to have some success in children and adults [60,61], and has been shown to be a successful weight reduction strategy among children with overweight [62] and adolescents [63]. Similarly it is possible to change eating rate indirectly through the use of food textures that are equally liked, but require longer chewing [11,13,18,43,58].…”
mentioning
confidence: 99%
“…However, just a few studies have investigated the role of common dietary behaviors in the development of obesity. Although some studies reported the positive relation between eating speed and obesity [7][8][9][10], such findings have not been confirmed by others [11]. Eating before bedtime has also been linked to weight gain [12], but not consistently [13].…”
Section: Introductionmentioning
confidence: 90%
“…Based on earlier studies [8,9,13], dietary behaviors were pre-defined and assessed in five domains (meal patterns, eating rate, intra-meal fluid intake, meal-to-sleep interval, and fatty food intake) using a self-administered questionnaire. Detailed information about the questions included in each domain as well as the response categories for each Table 1.…”
Section: Assessment Of Dietary Habitsmentioning
confidence: 99%